Efektivitas Perlindungan Hukum Bagi Korban Kekerasan Akibat Tindak Pidana Penganiayaan - Bunyamin, Bunyamin (Al-Ishlah: Jurnal Ilmiah Hukum, 2021)
This study aims to determine the effectiveness of legal protection for the victims of violence due to the criminal of mishandling in Bone Regency and the factors that influence it. In this study the researcher uses normative and empirical research which is descriptive and prescriptive. The process of collecting data in this study were through by interview, documentation, and also literature study. The analysis method is carried out by systematically identifying and connecting the primary data with the primary legal materials. The result of this study indicates that legal protection for the victim of violence due to criminal of mishandling in Bone Regency is still running less effective. In this point, mishandling case is tend to increase every day. In other hand there are still several cases that have not been completely resolved, which is by the police considered as lack of solid evidences. Likewise, there are still mishandling cases in the court that have not been resolved because they are still in process. In addition, the fulfillment of victims’ rights has not been fully implemented, such as the right to receive spiritual guidance services. So, even though the implementation of government’s obligation and law enforcement has been effective, it still needs to be improved in order to achieve the effectiveness of legal protection for the victims of mishandling criminal under the jurisdiction of Bone subregional police. The factors that influenced the effectiveness of legal protection for the victims of mishandling criminal in Bone Regency, namely the legal substance factor, legal structure factor, legal culture factor, facilities and infrastructure factor, legal knowledge factor, and legal awareness factor. Therefore, it is necessary to increase the professionalism of law enforcement towards officers, and fulfil the rights of the victims. In addition, the government and law enforcement must be maximized the providing of legal protection, especially by considering the factors that affect the effectiveness, so that legal protection can be optimally realized in the future.